Embryonic morphogenesis signaling pathway mediated by JNK targets the transcription factor JUN and the TGF-beta homologue decapentaplegic. - Sluss, H.K.; Davis, R.J. (Journal of Cellular Biochemistry, 1997)
The dorsal surface of the Drosophila embryo is formed by the migration of the lateral epithelial cells to cover the amnioserosa. The Drosophila cJun-N-terminal kinase (DJNK) is essential for this process. Mutations in DJNK or the DJNK activator hemipterous (HEP) lead to incomplete dorsal closure, resulting in a hole in the dorsal cuticle. The molecules downstream of DJNK in this signaling pathway have not been established. Here we demonstrate that the basket1 (bsk1) mutation of DJNK causes decreased interaction with DJUN. Expression of decapentaplegic (DPP), a TGF-beta homologue, in the leading edge of the dorsal epithelium, is identified as a genetic target of the JNK pathway. A constitutive allele of JUN is able to rescue the dorsal closure defect of bsk1 and restores DPP expression. Furthermore, ectopic DPP rescues the defects in dorsal closure caused by bsk1. These data indicate that the interaction of DJNK with DJUN contributes to the dorsal closure signaling pathway and targets DPP expression.